2022
DOI: 10.2478/johh-2021-0037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of slope position on soil properties and soil moisture regime of Stagnosol in the vineyard

Abstract: Hillslope hydrology in agricultural landscapes is complex due to a variety of hydropedological processes and field management possibilities. The aim was to test if there are any differences in soil properties and water regime along the hillslope and to compare vineyard rows (vine) with inter-rows (grass) area for those properties. The study determined that there are significant differences in the contents of soil particle fractions, pH, and humus content along the slope (P < 0.0001), with lower confidence l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 52 publications
(51 reference statements)
1
8
0
Order By: Relevance
“…This might be because clay particles were deposited at lower slope positions after being washed away from upper slope positions. In line with this finding, there have also been reports of higher clay content at lower slope positions relative to middle and upper slope positions [44,25,95,8,4,51]. This result was consistent with studies that found increased clay amount under cultivated land concerning forestry and grazing land [31,89,78,19].…”
Section: Particle Size Distributionsupporting
confidence: 91%
See 1 more Smart Citation
“…This might be because clay particles were deposited at lower slope positions after being washed away from upper slope positions. In line with this finding, there have also been reports of higher clay content at lower slope positions relative to middle and upper slope positions [44,25,95,8,4,51]. This result was consistent with studies that found increased clay amount under cultivated land concerning forestry and grazing land [31,89,78,19].…”
Section: Particle Size Distributionsupporting
confidence: 91%
“…The slope positions are a common factor in topography, and they expose how different soil properties, such as pH, organic matter content, and particle size distribution, depend on terrain characteristics [69, 52,51]. Parent material, terrain, temperature, vegetation, and human influences are among the components that affect the more sensitive soil qualities in the highland agro-ecological zone.…”
Section: Introductionmentioning
confidence: 99%
“…Soil physical and chemical differences among study sites can greatly influence the hydrology of the soils; however, in the present study, the differences in soil texture between sites were less pronounced than the heterogeneity within the same slope. Magdić et al [ 46 ] found similar results, reporting that the upper part of the vineyard slope had higher soil moisture content compared to the lower points. These authors also suggested that higher clay content could be a possible cause.…”
Section: Discussionmentioning
confidence: 67%
“…To determine weight loss, the samples were weighed using a digital balance (BCE224i-1SKR, Sartorius, Göttingen, Germany). The moisture content (%) of the potting soil was determined using the gravimetric method (Magdić et al, 2022 ). Moisture content (%) was calculated by the weight loss of the sample (50 g) maintained in a dry oven (DS-80-1, Dasol Scientific Co. Ltd., Hwaseong-si, Korea) at 105 °C until a constant weight was reached.…”
Section: Methodsmentioning
confidence: 99%